Effects of teleworking on wellbeing from a gender perspective: a systematic review - Castro-Trancón, Nereida; Zuazua-Vega, Mónica; Osca, Amparo; Cifre, Eva; García-Izquierdo, Antonio L. (Frontiers in Organizational Psychology, 2024)
Telework has been seen as a crucial tool for enhancing work-home balance, and potentially boosting employee wellbeing. However, contradictory findings highlight the necessity of integrating a gender perspective. This study aims to find out the psychosocial effects of teleworking on wellbeing from a gender perspective through a systematic review since 2010 till 2022. We used PRISMA, SPICE and PICOS models to finally select 37 studies, considering both quantitative and qualitative design perspectives. More than half of the reviewed articles (22) found that telework has negative effects on work-family interaction and work-family balance; and, as expected, these negative effects were greater for women, such as increasing dissatisfaction with work, life and free time. Studies reviewed show that women teleworkers report increased work-family conflict and traditional gender roles relating to household and family care responsibilities. We have found also that 10 studies observed positive effects of telework for both men and women, whilst five papers report both positive and negative effects on wellbeing. Lastly, we discuss the advantages and disadvantages of teleworking from a gender perspective considering the results we have found.